2021
DOI: 10.1002/mrc.5164
|View full text |Cite
|
Sign up to set email alerts
|

Azo‐hydrazone molecular switches: Synthesis and NMR conformational investigation

Abstract: A series of five intramolecularly hydrogen-bonded arylhydrazone (aryl = phenol, p-nitrophenol, anisole, quinoline) derived molecular switches have been synthesized and characterized by NMR and HRMS techniques. It was found that the compounds exist as different isomers in solution. An investigation of both conformational and/or configurational changes of the azo-hydrazone compounds was carried out by 1D 1 H-and 13 C-spectra, 2D NOESY, COSY, HSQC, and HMBC techniques. It was found that these stimuli-responsive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Nuclear shieldings can be difficult to calculate in negatively charged species due to large self-interaction errors [ 55 ]. In the case of the azo compound ethyl 2-(2-(2-hydroxyphenyl)hydrazineylidine)-2-(pyridin-2-yl)acetate (see Figure 26 ), the best agreement between the experimental 13 C chemical shifts and calculated ones was obtained with B3LYP/6-311++G(2d,p) + PCM and adding a water molecule, as seen in Figure 26 [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear shieldings can be difficult to calculate in negatively charged species due to large self-interaction errors [ 55 ]. In the case of the azo compound ethyl 2-(2-(2-hydroxyphenyl)hydrazineylidine)-2-(pyridin-2-yl)acetate (see Figure 26 ), the best agreement between the experimental 13 C chemical shifts and calculated ones was obtained with B3LYP/6-311++G(2d,p) + PCM and adding a water molecule, as seen in Figure 26 [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…78,79 Miyamoto and Hada 80 analyzed 13 C NMR chemical shifts in substituted benzenes using natural perturbation orbitals and substitution effects. Hansen et al 81 reported on the synthesis and NMR conformational characterization of azo-hydrazone molecular switches supported by GIAO NMR calculations. Erdog ˘an and Serdarog ˘lu 82 synthesized and characterized a novel pyrene-sulfathiazole-based potential drug candidate, (E)-4-((pyren-1-ylmethylene)amino)-N-(thiazol-2-yl)benzenesulfonamide.…”
Section: Dft Studies Of Nuclear Shieldingmentioning
confidence: 99%